Women Archetype Characters and Motifs in Three Indonesian Folk Tales - Riska Roslina Rosiana (Universitas Pendidikan Indonesia (UPI), 2013)
This study entitled Woman Archetype Characters and Motifs in Three Indonesian Folk Tales has three aims: 1) to identify the description of woman archetypes in Indonesian folk tales in term of the characters and motifs employed in the tales; 2) to investigate the representation of woman archetype of Indonesian folk tales with references to European folk tales; and 3) to make meaning from the comparison between Indonesian folk tales and their European counterpart. The study employs qualitative study with the content analysis approach. The analysis of the study is framed within the theory of archetype characters in literature proposed by Jung (1961), and the theory of archetype motifs in folk literature by Thompson (1955-1958). The fact that Indonesian women are presented to be more assertive and independent than their European counterpart rejects the stereotyped view of Indonesian women as submissive and dependent women. Keywords: woman, archetype, character, motif, folk tale